A multifaceted hospitalist quality improvement intervention: Decreased frequency of common labs. Issue 6 (21st March 2015) - Corson, Adam H.; Fan, Vincent S.; White, Travis; Sullivan, Sean D.; Asakura, Kenji; Myint, Michael; Dale, Christopher R.
<x xml:space="preserve">Abstract</x> PURPOSE Common labs such as a daily complete blood count or a daily basic metabolic panel represent possible waste and have been targeted by professional societies and the Choosing Wisely campaign for critical evaluation. We undertook a multifaceted quality‐improvement (QI) intervention in a large community hospitalist group to decrease unnecessary common labs. METHODS The QI intervention was composed of academic detailing, audit and feedback, and transparent reporting of the frequency with which common labs were ordered as daily within the hospitalist group. We performed a pre‐post analysis, comparing a cohort of patients during the 10‐month baseline period before the QI intervention and the 7‐month intervention period. Demographic and clinical data were collected from the electronic medical record. The primary endpoint was number of common labs ordered per patient‐day as estimated by a clustered multivariable linear regression model clustering by ordering hospitalist. Secondary endpoints included length of stay, hospital mortality, 30‐day readmission, blood transfusion, amount of blood transfused, and laboratory cost per patient. RESULTS The baseline (n = 7824) and intervention (n = 5759) cohorts were similar in their demographics, though the distribution of primary discharge diagnosis‐related groups differed. At baseline, a mean of 2.06 (standard deviation 1.40) common labs were ordered per patient‐day. Adjusting for age, sex, and principle discharge diagnosis, the number of common labs ordered per patient‐day decreased by 0.22 (10.7%) during the intervention period compared to baseline (95% confidence interval [CI], 0.34 to 0.11; P < 0.01). There were nonsignificant reductions in hospital mortality in the intervention period compared to baseline (2.2% vs 1.8%, P = 0.1) as well as volume of blood transfused in patients who received a transfusion (127.2 mL decrease; 95% CI, −257.9 to 3.6; P = 0.06). No effect was seen on length of stay or readmission rate. The intervention decreased hospital direct costs by an estimated 16.19 per admission or 151, 682 annualized (95% CI, 119, 746 to 187, 618). CONCLUSION Implementation of a multifaceted QI intervention within a community‐based hospitalist group was associated with a significant, but modest, decrease in the number of ordered lab tests and hospital costs. No effect was seen on hospital length of stay, mortality, or readmission rate. This intervention suggests that a community‐based hospitalist QI intervention focused on daily labs can be effective in safely reducing healthcare waste without compromising quality of care. Journal of Hospital Medicine 2015;10:390–395. © 2015 Society of Hospital Medicine